Analisis Peran Sastra dan Cerita Rakyat terhadap Pembentukan Karakter Peserta Didik di Era Globalisasi: An Analysis of the Role of Literature and Folklore in Shaping Students Character in the Era of Globalization - Yuga Bayu Prabowo; Jihan Nafisa Az-Zahra (Al-Absah: Journal of Civilization, Language, Literature, and History, 2025)
This study aims to analyze the role of literature and folklore in shaping students’ character in the era of globalization. Traditional literature, particularly folklore, has long been employed as a medium for instilling moral, religious, social, and cultural values that are closely related to everyday life. However, the rapid development of digital technology and the forces of globalization present serious challenges, as younger generations are increasingly exposed to global popular culture rather than local heritage. This research applies a library research method with a descriptive-analytical approach by examining primary and secondary sources, including scholarly articles, international reports, and digital content. The findings reveal that folklore remains relevant in character education because it conveys values such as honesty, responsibility, cooperation, courage, and respect for parents. On the other hand, digital globalization contributes to value shifts and cultural identity erosion among students. Therefore, revitalization strategies are necessary, particularly through adapting folklore into digital formats such as short films, digital comics, and multimedia content. This study concludes that literature and folklore continue to play a significant role in character education and will remain effective if creatively integrated into modern learning that is contextual with contemporary developments. Keywords: character, folklore, globalization, literature, local culture